The magmatic evolution of oceanic plateaus : a case study from the Azores - Beier, Christoph (2006)
The formation and evolution of oceanic plateaus (e.g. Ontong Java Plateau, Iceland) have often been associated with the presence of melting anomalies in the upper mantle. These are characterised by the large spatial distribution of volcanism erupted in relatively short periods of time. Against this background, the present doctoral thesis presents an investigation of the formation and evolution of the submarine Azores Plateau.The wide spatial distribution of eruptions from 4.9 to 6.0 Ma ago is a result of the arrival of a relatively small melting anomaly beneath the lithosphere leading to the eruption of tholeiitic and alkaline lavas. Higher degrees of partial melting and the occurrence of depleted ‘MORB’-like isotopic compositions suggest eruptions in the vicinity of the MAR spreading axis. The Sr-Nd-Pb isotope systematics reveals a small scale heterogeneous mantle beneath the Azores, where each volcanic structure is defined by a single isotopic range, with only very limited mixing between them.